Studies in law, politics, and society. Vol. 40 - Sarat, Austin (Elsevier JAI, 2007)
"Studies in Law, Politics and Society" continues the tradition of annually publishing interdisciplinary research on law with a critical focus that was begun in Research in Law and Sociology and carried forward in Research in Law, Deviance and Social Control. The new title describes an expanded focus and a broader audience of legal scholars who study: the intersection of legal thought and consciousness and the development of legal practices and institutions; and the development of legal thought and practices. The research spans a wide range of law related subjects including law and inequality, feminist jurisprudence, racial oppression and law, legal institutions and communities, and the ways law is used by political authorities or by ordinary citizens. Legal scholarship produced from an historical, comparative or ethnographic perspective is of special interest. This book series is available electronically online.